"We Look Ahead Where his Thoughts Never Reach": Pakistani Mothers' Agency to Expand Educational Opportunities for Their Daughters and the Theorisation of Negative Capability. Issue 1 (2nd January 2023) - Khalid, Aliya; Rose, Pauline
ABSTRACT: Juxtaposed against literature that views mothers' role for their daughters' education as a human capital this paper reimagines their role by foregrounding Pakistani mothers' agency in contexts with limited opportunities. This is achieved by theorising negative capability (NC) as an analytical framework drawing on available theorisations of the concept and define it as an agentive passive refusal to be intellectually paralysed by disadvantage . We demonstrate how the concept can be applied for empirical analysis. The paper takes an ethical stance that researchers should acknowledge that regardless of contextual difficulties people's agentive and intellectual faculties remain intact. Structural inequalities need to be challenged but their agentive potential also recognised. With a firm commitment that opportunities need to be made equal this paper builds on the second point to argue that even in the face of extreme disadvantage mothers' intellectual capacities to progress towards goals remain functional. We challenge the objectification of the marginalised and propose an analytical approach to understand difficulties faced as well as agency exercised by mothers facing socio-economic constraints. This work has implications for the capability approach that falls short of addressing issues of power, and policy that fails to understand the context.